2002
DOI: 10.1002/app.11555
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced GMA/DMAA graft copolymerization onto porous PE hollow‐fiber membrane

Abstract: Radiation-induced graft copolymerization is a powerful technique to prepare a grafted chain with the desired properties pending onto the trunk material. In this work, a polyethylene hollow-fiber membrane was modified by this technique. The monomers glycidyl methacrylate (GMA) and N,N-dimethylacrylamide (DMAA) were cografted onto macroporous polyethylene hollow fiber with a grafting degree in the order of 200%. DMAA/GMA cografted membranes were compared to GMA grafted ones for the introduction of an amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The polymerisation step brings about an increase of 27 to 35% in the unmodified membrane weight. The results in Table 1 indicate that the degree of grafting becomes higher as the proportion of DMAA in the monomer mixture increases; however, it was reported that such a difference in the degree of grafting does not play an important role in the subsequent coupling steps [10]. Those mass add-in quantities spread on a high internal surface area (15 m 2 /g, dry weight), thus effecting only a minimum change in the internal pore diameter.…”
Section: Preparation Of Cibacron Blue F3g-a Hollow-fibre Membranesmentioning
confidence: 93%
See 4 more Smart Citations
“…The polymerisation step brings about an increase of 27 to 35% in the unmodified membrane weight. The results in Table 1 indicate that the degree of grafting becomes higher as the proportion of DMAA in the monomer mixture increases; however, it was reported that such a difference in the degree of grafting does not play an important role in the subsequent coupling steps [10]. Those mass add-in quantities spread on a high internal surface area (15 m 2 /g, dry weight), thus effecting only a minimum change in the internal pore diameter.…”
Section: Preparation Of Cibacron Blue F3g-a Hollow-fibre Membranesmentioning
confidence: 93%
“…Well-resolved carbonyl IR signal areas at 1600 -1665 cm -1 and 1700 -1765 cm -1 corresponding to DMAA and GMA respectively were used to estimate the copolymer composition. A calibration curve correlating the ratio of carbonyl IR signal areas and known monomer mixtures was previously performed as described in reference [10]. We assumed the carbonyl IR signal ratio of the monomer mixture samples and the carbonyl IR signal ratio of the grafted copolymer samples to be similar.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations